Broken Arrows. (26th October 2008) - Furon, Teddy; Bas, Patrick
Abstract : This paper makes an account of the design and investigations done for the still image watermarking technique used in the 2nd edition of the BOWS challenge. This technique is named "broken arrows" for some reasons given later on, and abbreviated "BA." This zero-bit algorithm is an implementation of a recent theoretical result by Merhav and Sabbag (2008) with precautions taken with respect to robustness, security, and imperceptibility. A new robustness criterion, based on the nearest border point of a cone, is proposed. The security constraint is taken into account by increasing the diversity of the watermark, sculpturing and randomizing the shape of the detection regions. The imperceptibility and robustness are also provided by adopting proportional embedding in the wavelet domain. The algorithm has been benchmarked using a database of 2000 images. For a probability of false alarm below3 ⋅ 10 − 6 and a PSNR of 43 dB, the overall robustness regarding various classical image processing seems a promising and strong basis for the challenge.